A produção textual no livro didático de língua portuguesa: discutindo o ensino da linguagem - Santiago, Alessandra Cristina Santos (2015)
The present study dealt with the relation between the Portuguese Language Textbook and the Written Language Teaching according to the literacy perspective. The study is justified, on the one hand, by finding the increasing difficulties of educated people in using writing, adequately, in different sociocommunicative environments, and on the other hand, by the importance of the textbook in the classroom as a regulatory tool of the pedagogical action. The research tried to understand how the language practice activities guidelines (reading and text production) proposed in the Portuguese Language Textbooks of the PNLD-2014 contribute to the acquisition of the written language as a cultural activity of social interaction. For this purpose, we chose to perform a qualitative research in the form of documentary research. The Analysis was based on the contributions of Vygotsky and Bakhtin about language and studies on literacy according to Soares, Kleiman and Rojo. The research results indicated that the Portuguese Language Texbooks, although adopting language conceptions that consider the language in its discursive form, yet, propose activities which do not favor the formation of a critical and reflexive reader and writer.